Narrative accounting for mining in Ghana: An old defence against a new threat?. (December 2021) - Amoako, Kwame Oduro; Lord, Beverley R.; Dixon, Keith
Abstract: This article is concerned with aspects of how accounting and accountants figure in economics and policy issues related to mineral and fossil fuel extraction, production and use. Starting by appraising whether narrative accounting by a transnational mining corporation is attuned to the people working or living in an area affected by the mining operations, it goes on to considering how data, calculations and communications pertaining to sustainability are applied. This includes what connections the people involved perceive between accounting and sustainability. Data were obtained through qualitative fieldwork in and around the Damang Mine in Ghana, comprising interviews with employees and in the community, and analysis of documents. Corporation executives use narrative accounting to back claims that they invest hugely in sustainability, so having, in their words, a social licence to operate from host community stakeholders . This reflects accounting figuring in resource allocation choices, including in terms of how shareholder capital is managed to generate greater societal value and to operate sustainably. However, although many local people see themselves as deriving some benefit from the socio-economic activities of the mining corporation, they see accounting as not their business, being more economic than environmental or social. The inference is that accounting continues to serve purposes of management control of production, distributing value-added in favour of capital providers and managing image reflected in the notion of having a social licence to operate. Despite their belief that accounting and accountants having roles to play in sustainability, they generally cannot identify these roles. These findings imply that, if account providers are serious about being corporately responsible towards affected people, they must do more to ensure that environmental and social aspects receive enough attention to convince those people that they are truly being engaged with on equal terms, in addition to convincing a wider audience that the reports they produce are reliable and relevant to sustainability in practice. Highlights from the study: Corporation executives use narrative accounting to back claims that they invest hugely in sustainability. Although external stakeholders see accounting as not their business, being more economic than environmental or social. External stakeholders belief that accountants have roles to play in sustainability, they generally cannot identify these roles. Unfortunately, accounting continues to serve purposes of managing image reflected in the notion of having a social licence to operate.